Physical activity and sedentary behaviours among grassroots football players: A comparison across three European countries - Van Hoye, A.; Fenton, S.; Krommidas, C.; Heuzé, J.; Quested, Eleanor; Papaioannou, A.; Duda, J. (2013)
The purpose of the present study was to determine and compare the levels of objectively assessed physical activity (PA) and sedentary time (ST) among male players aged 10-14 who participate in grassroots football in three European countries (i.e. England, France, and Greece). In addition, the study also examined the relationship of objective levels of PA to a self-report measure of PA frequency used in the Health Behaviour in School-aged Children survey for young football players. A total of 331 participants provided at least three days of valid accelerometer data and completed a self-report measure of PA. The results revealed that players accumulated 122.33 minutes of moderate- to vigorous PA (MVPA) and 488.19 minutes of ST per day. Multiple analyses of covariance controlling for years of experience in football revealed slightly significant differences between the three countries for light PA, MVPA, and the number of active days defined as meeting the [World Health Organization. (2010). Global recommendations on physical activity for health. Geneva: Author. Retrieved from http://whqlibdoc.who.int/publications/2010/9789241599979_eng.pdf] guidelines of 60 minutes of MVPA per day. English participants spent less time in light PA but more time in MVPA than the Greek or French players. Greek participants had more active days than their English and French counterparts. The self-report measure of PA was not significantly associated with objective PA in this sample of male football participants. Findings suggest that young Europeans who play football meet WHO guidelines for MVPA, but their adoption of an active lifestyle might not protect them from ST behaviours. © 2013 International Society of Sport Psychology.